Syringocystadenoma papilliferum mimicking basal cell carcinoma on the lower eyelid: a case report - Askar, Ibrahim; Kilinc, N; Aytekin, S (Acta chirurgiae plasticae (English ed.), 2002)
Background. Syringocystadenoma papilliferum is an unusual benign tumor most commonly located on the scalp or face, which frequently arises from a nevus sebaceous. Transition of SP to basal cell carcinoma and, rarely, to metastatic adenocarcinoma may occur. Case Report. A 28-year-old female patient had been suffering from a pinkish, painless nodule for 25 years. Physical examination revealed a pinkish, non-tender, painless nodule, 5mm in diameter, on the lower eyelid. The nodular lesion was excised, and the lower eyelid was reconstructed with V-Y advancement Tlap. Histopathologic examination revealed hyperkeratosis with papillomatosis of epidermis. The dermis showed several cystic invaginations extending downwards from the epidermis. One year tater, the postoperative result was cosmetically and functionally acceptable. Conclusion. Syringocystadenoma papilliferum mimicking basal cell carcinoma on the lower eyelid is of interest, since there were scanty skin appendages. Our paper considers the issue of differentiating between SP and BCC, since SP is asymptomatic and may have similar appearance. We believe that SP may be a transitional step from nevus sebaceous to basal cell carcinoma, since molecular studies show PTCH Bene in alt three lesions, the origins of SP are still debatable, and both SP and BCC can arise in nevus sebaceous of Jadassohn.
Keywords: bazocelulární karcinom; Carcinoma, Basal Cell; Eyelid Neoplasms; lidé; Female; ženské pohlaví; Adenoma, Sweat Gland; Humans; nádory očního víčka; adenom potní žlázy